Aprendizaje a través de evaluaciones en las ONGD españolas: ¿una utopía? - Stock, Inka (Revista Española de Desarrollo y Cooperación, 2023)
The aim of this article is to document and describe current evaluation practice in Spanish Non Governmental Development Organisations (NGDOs) and examine practitioner’s views on learning through evaluation. It is based on results of a qualitative research project of members of 19 NGDOs that contribute to current debates on the application of the concept of evaluation in development assistance. The study demonstrates that evaluation is a sporadic activity in Spanish NGDOs and not efficiently used for organisational learning. There are institutional, contextual and personal obstacles that lead to this situation, but it is considered that NGDOs themselves could cause positive changes through the adaptation of their organisational structures and procedures, the dedication of new technical, human and financial resources for evaluation and the promotion of a working culture based on auto-critique and internal reflection.